Elegant ecstasies metropolitan fantasies and gay desires in Carlomar Arcangel Daoana's The Fashionista's Book of Enlightenment - Serquina, Oscar Tantoco Jr. (2013)
In a close reading of Carlomar Arcangel Daoana's The Fashionista's Book of Enlightenment, it is observed that his poems render excessiveness, affluence, beauty, and glamour as main thematic ways of problematizing the gay figure situated in the city and whose life moves between the poles of loss and love. This essay initiates a critical reading of the poems within the proposed ambits of metropolitan fantasies and gay desires in order to plot out their conspicuous upper/middle class and Western(ized) aesthetic, reveal their intimacies and imitations with an Other that does not only allude to a global audience but also to the desired objects gay men have, and critique a poetry that is predicated largely on consumerism, fabulousness, and sexual/sensual bodies.
Keywords: Philippine poetry